2020
DOI: 10.31557/apjcp.2020.21.5.1247
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Eco-Friendly Naturally Synthesized Silver Nanoparticles from the Leaf Extract of Medicinal Detarium microcarpum Plant on Pancreatic and Cervical Cancer Cells

Abstract: This research field has received tremendous attention from researchers because of the many applications of the synthesized nanomaterials in medicine, telecommunication, engineering, and textile industry, to mention but a few (Hanan et al., 2018). In Medicine, nanoparticles are used in drug development and delivery. The nanoparticles are used for the delivery of drug to a specific target in cells, tissues or organs. Nanoparticles can as well be used for infectious disease and cancer therapy (Thakkar et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…As a result, anti-breast cancer compounds may be found in the stem bark of these plants [ 59 ]. dAgNps inhibited HeLa cell proliferation with IC 50 values of 31.5 μ g/mL [ 79 ]. The chloroform and ethyl acetate extracts were the most effective at inhibiting osteosarcoma cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, anti-breast cancer compounds may be found in the stem bark of these plants [ 59 ]. dAgNps inhibited HeLa cell proliferation with IC 50 values of 31.5 μ g/mL [ 79 ]. The chloroform and ethyl acetate extracts were the most effective at inhibiting osteosarcoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…HeLa cell growth was decreased by dAgNps with IC 50 values of 31.5 μg/mL. [79] Notes: S/N � serial number.…”
Section: Aqueousmentioning
confidence: 99%
“…Silver nanoparticles synthesized from phytochemicals (plant compounds) have been found to have antimicrobial, anticancer, antioxidant, and antidiabetic properties [ 15 ]. For instance, silver nanoparticles synthesized from the phytochemicals of Alternanthera sessilis, Dendrophthoe falcata, Albizia adianthifolia, Morinda citrifolia, Detarium microcarpum, and Artemisia turcomanica were reported to have antiproliferative effects on the growth of prostate cancer (PC3), breast cancer (MCF7), lung cancer (A549), cervical cancer (HeLa), pancreatic cancer, and gastric cancer (AGS) cells, respectively [ 14 , 16 20 ]. Hence, owing to the fact that there is a pressing need for effective therapy for leukemia, in this study, we investigated the potency of the silver nanoparticles synthesized from B. dalzielii stem bark metabolites to inhibit the growth and proliferation of AML cell line, Kasumi-1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of special clinical manifestations in the early stage of pancreatic cancer, the disease has reached the middle and late stage when most patients are diagnosed clinically, and only 15%~20% of patients can be treated with surgical resection, and about 50% of patients can be complicated with distant metastasis (3). The incidence of pancreatic cancer is related to genetic and environmental factors (4). Previous studies have shown that chronic pancreatitis, family inheritance and smoking can increase the risk of pancreatic cancer (5,6).…”
Section: Introductionmentioning
confidence: 99%